ORGANIZATIONAL COMMUNICATION OF THE KUPANG CITY REGIONAL INFLATION CONTROL TEAM IN MAINTAINING INFLATION STABILITY: (ANALYSIS OF COMMUNICATION PATTERNS IN INFLATION CONTROL DECISION MAKING AT THE KUPANG CITY TPID HIGH LEVEL MEETING FORUM) - Windi Putri Elisabeth Fanggi; Iriana Bakti; Trie Damayanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Regional inflation control requires cross-agency coordination that is not only structural in nature but also fundamentally communicative. This study aims to analyze the dynamics of organizational communication within the Regional Inflation Control Team (TPID) of Kupang City by examining differences in communication patterns between the policy formulation phase and the policy implementation phase. The research employs a Social Network Analysis (SNA) approach to map the communication structure among TPID actors, grounded in a structuralism paradigm. Data were collected through in-depth interviews, observations of TPID meetings, and analysis of official documents. The findings reveal two distinct communication models: Model A, which is hierarchical and centralized during the policy meeting phase, and Model B, which is horizontal and collaborative during the policy implementation phase. These results underscore that organizational communication within TPID is dynamic and contextual, adapting to the specific policy function being carried out. This study contributes to the fields of organizational communication and public policy by demonstrating how communication operates as a working mechanism within cross-agency groups for regional inflation control.